(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The diversity of Indonesian society is reflected in the diversity of religions adhered to. Religious diversity also exists within the scope of the school, where students must be accustomed to having a value of tolerance and respect for each other as a form of implementation of Pancasila values. The purpose of this study was to find out how the implementation of Pancasila values in strengthening the values of interreligious tolerance among students at 3 Bae Kudus Junior High School. Research is a type of qualitative research with a case study approach. Data was obtained through observation, interviews, and documentation studies. Data analysis techniques use the Milles and Huberman techniques through data reduction, data presentation, concluding, and verification